2016
DOI: 10.1590/1679-78253066
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adherend Surface Roughness on the Adhesive Bond Strength

Abstract: Surface treatment of the adherends prior to adhesive bonding plays an important role in the enhancing of strength and durability of bonded joints. In this work, an investigation on effect of adherend surface roughness on adhesive bond strength was performed. Single strap joints with different adherends (mild steel and aluminium) bonded with an epoxy resin (Araldite® 2015) were tested. The adherend surface was treated by mechanical abrasion process using an emery paper. Contact angle measurement and SEM analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 29 publications
2
43
0
1
Order By: Relevance
“…One of the first attributes detected when comparing polycarbonate to tempered glass and aluminum print beds is that the polycarbonate has a noticeably rougher surface, as can be seen in the optical microscopic images in Figure 5a; this will likely be very helpful in bonding with the deposited materials [40][41][42][43][44][45][46]. In order to objectively compare the surfaces, a PosiTector ® surface profile gauge was used to measure the mean surface roughness at 100 random points on the surface of the polycarbonate, as well as on the bare aluminum and tempered glass beds.…”
Section: Surface Profile Comparison Experimentsmentioning
confidence: 99%
“…One of the first attributes detected when comparing polycarbonate to tempered glass and aluminum print beds is that the polycarbonate has a noticeably rougher surface, as can be seen in the optical microscopic images in Figure 5a; this will likely be very helpful in bonding with the deposited materials [40][41][42][43][44][45][46]. In order to objectively compare the surfaces, a PosiTector ® surface profile gauge was used to measure the mean surface roughness at 100 random points on the surface of the polycarbonate, as well as on the bare aluminum and tempered glass beds.…”
Section: Surface Profile Comparison Experimentsmentioning
confidence: 99%
“…It is well known that sand-blasting or plasma spraying method is applied to increase the surface roughness of Ti implants [15,16]. An appropriate surface roughness results in an improved mechanical interlock between the Ti implant and bone tissue [17,18]. For chemical etching, alkaline treatment, and chemical deposition methods, many reports have demonstrated that the surface morphology and chemical composition of Ti implants could be modified effectively [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In an adhesive joint, adhesive are applied between two plates (known as adherends). Adhesive bonding of metal-to-metal accounts for less than 2% of the total metal joining applications [2].…”
Section: Introductionmentioning
confidence: 99%
“…Material properties and geometry size were investigated significantly to see effect on the joint strength and failure modes. On account of the effect of factors mentioned above, A. Ghumatkar [2] focused on improving the strength of the joints. The joint strength in-creased by modifying the shape of the joint and adding chamfer and fillets.…”
Section: Introductionmentioning
confidence: 99%